(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the transformative consequences of AI on economic structures, labor markets, productivity, and wealth distribution. Unlike previous technological shifts, AI’s capacity for autonomous decision-making and continuous learning introduces unprecedented efficiency gains while simultaneously challenging traditional employment models. This study examines how AI-driven automation, data-driven decision-making, and algorithmic innovation are redefining economic principles, creating new sectors, and altering the dynamics of global competition. While AI promises enhanced productivity and economic expansion, it also raises concerns about labor displacement, income inequality, and regulatory challenges. Ultimately, we argue that the success of this transformation hinges on strategic policy frameworks, adaptive workforce strategies, and ethical AI deployment.